2000
DOI: 10.2307/121047
|View full text |Cite
|
Sign up to set email alerts
|

Chern Numbers for Singular Varieties and Elliptic Homology

Abstract: A fundamental goal of algebraic geometry is to do for singular varieties whatever we can do for smooth ones. Intersection homology, for example, directly produces groups associated to any variety which have almost all the properties of the usual homology groups of a smooth variety. Minimal model theory suggests the possibility of working more indirectly by relating any singular variety to a variety which is smooth or nearly so.Here we use ideas from minimal model theory to define some characteristic numbers fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 26 publications
1
70
0
Order By: Relevance
“…Presumably there is some simultaneous generalization that applies to higher elliptic genera. Some useful references that discuss elliptic genera in the context of birational geometry are [47], [9], [10], [11], [13], [45]. (2) Are there examples that show that our vanishing theorem for higher Todd genera are false for finite π, if one does not rationalize?…”
Section: Connections To Group Actionsmentioning
confidence: 99%
“…Presumably there is some simultaneous generalization that applies to higher elliptic genera. Some useful references that discuss elliptic genera in the context of birational geometry are [47], [9], [10], [11], [13], [45]. (2) Are there examples that show that our vanishing theorem for higher Todd genera are false for finite π, if one does not rationalize?…”
Section: Connections To Group Actionsmentioning
confidence: 99%
“…Elliptic genus appears to be a key tool for a solution to this problem. In [30] it was shown that the Chern numbers invariant in small resolutions are determined by the elliptic genus of such a resolution. In [7] the elliptic genus was defined for singular varieties with Q-Gorenstein, Kawamata-logterminal singularities and its behavior in resolutions of singularities was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Since the elliptic genus depends only on the Chern numbers, it is a cobordism invariant. Totaro [30] found a characterization of the elliptic genus (2) of SU-manifolds from the point of view of cobordisms as the universal genus invariant under classical flops.…”
Section: Introductionmentioning
confidence: 99%
“…The proof in [31], that there is no other genus preserved by flops (or equivalently, satisfying φ(E) = 0 for any fibre bundle E CP (3)…”
Section: Equivariant Genera Of the Loop Spacementioning
confidence: 99%